2014
DOI: 10.1111/flan.12064
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Study Abroad Homestay Placements: Participant Perspectives and Oral Proficiency Gains

Abstract: Although the study abroad homestay context is commonly considered the ideal environment for language learning, host‐student interactions may be limited. The present study explored how language development of students of Spanish, Mandarin, and Russian related to student and host family perspectives on the homestay experience. The study used pretest and posttest Simulated Oral Proficiency Interviews to investigate student oral proficiency gains and surveys to examine beliefs of these students (n = 152) and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…Hosts also play a role in engaging with their student and can take an active role in the students’ learning [23]. Preparing students and hosts before the experience can encourage the necessary actions to lead to the educational opportunities a homestay has to offer [11,15]. When students do engage with their hosts, they become more integrated into the family and have closer access to cultural experiences, depending on the depth of their relationship [12].…”
Section: Discussionmentioning
confidence: 99%
“…Hosts also play a role in engaging with their student and can take an active role in the students’ learning [23]. Preparing students and hosts before the experience can encourage the necessary actions to lead to the educational opportunities a homestay has to offer [11,15]. When students do engage with their hosts, they become more integrated into the family and have closer access to cultural experiences, depending on the depth of their relationship [12].…”
Section: Discussionmentioning
confidence: 99%
“…Even in terms of foreign language gains, it is reported that in some situations only modest improvements are found to be correlated with studying abroad (Freed, 1998;Freed, Segalowitz, & Dewey, 2004;Segalowitz et al, 2005). Recent findings have noted that the students' prior foreign language proficiency and their being home-stayed or locally immersed during study abroad, as far more important predictors of language gain (Di Silvio, Donovan, & Malone, 2014;Wilkinson, 1998). Even more surprising is that some research have shown that locally held foreign language immersion programs are said to be more effective than studying abroad (Freed et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Because of these mixed results, recent literature, such as Knight and Schmidt‐Rinehart () has looked at the quality of students’ relationship/interactions with their host families and at pedagogical interventions that could enhance learner–host family relationships and communication, such as shared‐time maximization or the completion of conversation assignments that follow a task‐based language teaching framework (e.g., Ellis, ). To gain insights concerning the nature of exchanges between learners and host families, most of these studies have employed qualitative methods: personal interviews, questionnaires, journals (Knight & Schmidt‐Rinehart, ), e‐journals (e.g., Stewart, ), and online surveys (e.g., Di Silvio et al, ; Shiri, ). Evidence has suggested that task‐based assignments can increase the likelihood that learners will maintain a better, more beneficial relationship with their host families (Knight & Schmidt‐Rinehart, ).…”
Section: Internal and External Variables: Toward A Multidimensional Amentioning
confidence: 99%